2010
DOI: 10.3109/14653240903446902
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of human dendritic cells labeled for in vivo 19F magnetic resonance imaging cell tracking

Abstract: Background aims Dendritic cells (DC) are increasingly being used as cellular vaccines to treat cancer and infectious diseases. While there have been some promising results in early clinical trials using DC-based vaccines, the inability to visualize non-invasively the location, migration and fate of cells once adoptively transferred into patients is often cited as a limiting factor in the advancement of these therapies. A novel perflouropolyether (PFPE) tracer agent was used to label human DC ex vivo for the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 49 publications
(77 reference statements)
3
114
1
Order By: Relevance
“…Cell product release criteria included thresholds for bacterial contamination, the presence of endotoxins, and cell viability. Nuclear magnetic resonance (NMR) was used to assay the 19 F content of the DCs after PFC labeling (4,6). Briefly, cell pellets containing a known cell number ($3 Â 10 6 ) were lysed with 1% Triton X-100 (Arcos Organics), and 0.1% (v/v) trifluoroacetic acid (TFA, Sigma-Aldrich, St Louis, MO) was added as an NMR reference compound.…”
Section: Preparation and Pfc Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell product release criteria included thresholds for bacterial contamination, the presence of endotoxins, and cell viability. Nuclear magnetic resonance (NMR) was used to assay the 19 F content of the DCs after PFC labeling (4,6). Briefly, cell pellets containing a known cell number ($3 Â 10 6 ) were lysed with 1% Triton X-100 (Arcos Organics), and 0.1% (v/v) trifluoroacetic acid (TFA, Sigma-Aldrich, St Louis, MO) was added as an NMR reference compound.…”
Section: Preparation and Pfc Labelingmentioning
confidence: 99%
“…The 19 F spectra display two narrow major peaks, one each for PFC and TFA, with a chemical shift difference of À15.58 ppm. The ratio of the integrated areas under these two peaks was used to calculate the mean 19 F/cell, as described previously (4,6). Cells were assayed for viability, using a standard trypan blue exclusion method.…”
Section: Preparation and Pfc Labelingmentioning
confidence: 99%
“…25,26 Other investigators have also reported on the ability to ex vivo label other potential cell therapies with 19 F, including murine 30 and human neural stem cells, 31 human CD34 C hematopoietic stem cells (HSCs) and mouse bone marrow derived HSCs as well as murine 32 and human 33 19 F-MRI without apparent toxicity. 34 About 10 million DCs were injected intradermally into quadriceps and patients were imaged for about 9.5 min.…”
mentioning
confidence: 99%
“…Interesting building blocks in the design of the nanoparticles' monolayer are perfluoropolyethers, these compounds are being extensively studied as 19 F MRI tracers in vitro and in vivo [49][50][51] and the data support a limited toxicity. Given the low cytotoxicity of these systems, application for cell tracking in vivo could be foreseen in analogy to nanoemulsion containing perfluoropolyether (PFPE) described by Ahrens [52,53].…”
Section: Toxicity Of Fluorous Gold Nanoparticlesmentioning
confidence: 99%